OPTIMIZATION OF HYDROGEN PURIFICATION USING A TEMPERATURE SWING ADSORPTION SYSTEM (TSA) METHOD BY VARYING TEMPERATURE AND PRESSURE - Huda, Hairul (Jurnal Chemurgy, 2025)
Industrial processes require hydrogen with more than 99% purification so that it can be used for various subsequent processes. Hydrogen purification using a two-pronged PSA system is simulated using Aspen Adsorption software by varying temperature and pressure to obtain high hydrogen purity. And can be done by Purification using TSA (Temperature Swing Adsorbent). Purification using TSA (Temperature Swing Adsorbent) is used to simulate heavy carbonation on a large scale, due to the different nature of the concentration of components to be separated TSA Considering that hydrogen decay is part of the overall network for mobility pathways. The aim of this research is to improve hydrogen purity by exploring effective processes and methods and identifying how temperature and pressure affect hydrogen purity. The exothermic reactions involved in this process tend to be weak due to thermodynamic properties that decrease at low temperatures, resulting in slow reaction kinetics. The exothermic reaction is weak, due to thermodynamics it melts at low temperatures, where the process is characterized by too low kinetics. Industrially, the process is divided into two stages, the first is carried out at lower to high temperatures on zeolite and activated carbon catalysts, where up to 99% TSA has lower operating pressures and operating costs but higher initial costs than PSA. Optimization results of system separation (H₂/CO₂/CH₄/CO/N₂ = 0.564/ 0.031/ 0.266 / 0.084/ 0.055) with a two-bed TSA process using two layers with activated carbon and zeolite adsorbents at a temperature of 298.15 and obtained purity with compositions ranging in H₂ of 99.99%, CO₂ of 0.043%, CH₄ of 0.0085 %, CO of 0.043%, and N₂ of 0.02%. Hydrogen purification with the TSA system is not widely used due to high energy consumption and large adsorbent supplies. the cycle is very long as a result of the time-consuming heating and cooling process which leads to a larger amount of adsorbent and a higher investment required for the process. However, this method is chosen when high product purification cannot be achieved with PSA.